Routledge handbook of research methods in military studies - Soeters, Joseph; Shields, Patricia M.; Rietjens, Sebastiaan (Routledge Handbooks, 2014)
The Routledge Handbook of Research Methods in Military Studies offers a comprehensive and dynamic overview of these developments as they emerge in the many approaches to military studies. The chapters in this Handbook are divided over four parts: starting research, qualitative methods, quantitative methods, and finalizing a study, and every chapter starts with the description of a well-published study illustrating the methodological issues that will be dealt with in that particular chapter. Hence, this Handbook not only provides methodological know-how, but also offers a useful overview of military studies from a variety of research perspectives. This Handbook will be of much interest to students of military studies, security and war studies, civil-military relations, military sociology, political science and research methods in general